Impact of denture cleansers on the color stability, surface roughness, microhardness, and antibacterial activity of PMMA denture base materials reinforced with titanium dioxide nanoparticles - Ibrahim Hamad Alfahdawi (Discover Applied Sciences)
Abstract Objective This study aimed to assess the effects of various denture cleansers on the color stability, surface roughness, microhardness, and antibacterial activity of polymethyl methacrylate (PMMA) denture base materials modified with titanium dioxide TiO2 nanoparticles. Materials and methods Ninety disc-shaped PMMA specimens (10 × 10 × 2 mm) were fabricated and divided into three groups based on TiO2 concentration: 0% (control), 3%, and 5%. Each group was further subdivided based on the cleanser used: distilled water, Corega oxygenating tablets, or 0.5% sodium hypochlorite (n = 10). Measurements of color change (ΔE, using the CIE Lab* system), surface roughness (Ra), microhardness (Vickers hardness test), and antibacterial activity (zone of inhibition against Streptococcus mutans and Candida albicans) were conducted at 90 and 180 days. Statistical analysis included one-way ANOVA and Tukey’s post hoc test (α = 0.05). Results Sodium hypochlorite induced the most significant color changes and surface roughness, particularly in the unreinforced group. TiO2-reinforced samples demonstrated improved resistance to surface degradation and maintained higher microhardness values, especially with 5% nanoparticle concentration. Chemical cleansers reduced antibacterial activity slightly, but TiO2-containing samples still exhibited superior efficacy compared to controls. Conclusion The incorporation of TiO2 nanoparticles enhances the durability, aesthetic stability, and antimicrobial properties of PMMA denture base materials. However, cleanser selection plays a critical role in preserving these properties. Sodium hypochlorite, while effective, may compromise surface integrity. Enzymatic and non-abrasive cleansers are more suitable for long-term use with nanoparticle-reinforced denture bases.